Factors affecting college dance teachers’ competency in Hainan province - Lin, Baiyun; Boonphadung, Suttipong; Siththada, Thada (Edelweiss Applied Science and Technology, 2025)
Dance teacher competency is crucial for ensuring high-quality dance education, prompting this study to investigate the factors affecting college dance teacher competency in Hainan Province. Employing a mixed-methods approach, quantitative data from a questionnaire survey of 504 dance teachers across 17 colleges, selected via simple random sampling, were analyzed using mean scores, standard deviations, and stepwise multiple regression to assess the levels and predictive impact of seven factors. Moreover, this study was complemented by qualitative interviews with nine experts to explore challenges and practical implications. Findings indicate all seven factors: practical experience, training experience, teaching experience, self-efficacy, school policy, teaching conditions, and social support. These factors are perceived at high levels (mean range: 3.63–3.87), with social support (β = 0.262), teaching conditions (β = 0.183), and teaching experience (β = 0.172) as the strongest predictors, explaining 51.0% of competency variance. This research offers targeted strategies for enhancing dance teacher competency, contributing to the advancement of regional dance education in Hainan Province.